Rome in the East - Ball, Warwick., author.
1 online resource (xli, 551 pages)
Keywords: "Rome in the East is an arresting study of the influence of Near Eastern culture on the Roman world, which overturns received wisdom about the spread of European culture to the East. It explores Roman archaeological and architectural remains in the Near East, and includes a survey of the presence of Rome beyond the imperial frontiers eastwards as far as Iran, India, Central Asia and China. The Near Eastern client kingdoms under Roman rule are examined in turn and each are shown to have affected Roman, and ultimately European, history in different but very fundamental ways"--